The Progressive Study of Various Risk Factors on Insulin Resistance in Type 2 Diabetic Mellitus - Ashish Shukla, Yogesh Kumar Rai, (International Journal of Innovative Research in Medical Science, 2017)
Objective - The current study have undertaken to explore the effect of various factors like non vegetarian diet, alcohol consumption, smoking and lack of physical activates which will going to an increased risk of insulin resistance Material and Method - The study were conducted 78 subjects of type 2 diabeties in urban and rural area of meerut city. Fasting plasma glucose, fasting plasma insulin and HOMA- IR were analyzed. Three groups of subjects were made according to no of risk factor associated with insulin resistance. Results - The study showed that Maximum HOMA-IR value were find in group c (Non- Vegetarian, Alcoholic, smoker with less physical work activates subjects) as compared to group a (Non- Vegetarian) and group b (Non- Vegetarian with Alcoholic). It is also found there were significant correlation between HOMA-IR value and no of risk factors p < 0.001. Conclusion - There is convincing evidence that non vegetarian diet, alcohol consumption, smoking and less physical activates are related to an increased risk factors for insulin resistance in type 2 diabetes. The study concluded a significant progressive relationship between number of risk factor with respect to HOMA-IR levels which is an indices of insulin resistance.